Adversity, cannabis use and psychotic experiences: evidence of cumulative and synergistic effects. (May 2014) - Morgan, Craig; Reininghaus, Ulrich; Reichenberg, Abraham; Frissa, Souci; ,; Hotopf, Matthew; Hatch, Stephani L.
Abstract : Background: There is robust evidence that childhood adversity is associated with an increased risk of psychosis. There is, however, little research on intervening factors that might increase or decrease risk following childhood adversity. Aims: To investigate main effects of, and synergy between, childhood abuse and life events and cannabis use on odds of psychotic experiences. Method: Data on psychotic experiences and childhood abuse, life events and cannabis use were collected from 1680 individuals as part of the South East London Community Health Study (SELCoH), a population-based household survey. Results: There was strong evidence that childhood abuse and number of life events combined synergistically to increase odds of psychotic experiences beyond the effects of each individually. There was similar, but weaker, evidence for cannabis use (past year). Conclusions: Our findings are consistent with the hypothesis that childhood abuse creates an enduring vulnerability to psychosis that is realised in the event of exposure to further stressors and risk factors.